2020
DOI: 10.9734/jpri/2020/v32i2830878
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Urinary Tract Infection among Diabetic Patients in Abakaliki Metropolis

Abstract: The investigation of urinary tract infection (UTI) among diabetic patients 15-51 years and above was assessed using 100 mid-stream urine specimen with the objective of isolating and identifying different types of bacteria and their respective frequencies among diabetic patients attending diabetic clinic at Alex Ekwueme Federal University Teaching Hospital, Abakaliki. A urine culture was performed combined with a full report of urine to establish the diagnosis. The result showed that the majority of bacteria in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…In Nigeria, the prevalence of UTI tend to vary depending on the study population and risk factors. For instance, a prevalence of 61.0% was reported among pregnant women (13) while a prevalence of 46% was reported in diabetic patients in Abakaliki (14). Among HIVinfected children and adolescents, a prevalence rate of 32.5% was reported (15) while 43.6% rate was reported in the general population without reported risks for UTI (16).…”
Section: Prévalence Des Infections Urinaires Symptomatiques Et Spectre Bactérien Des Patients Diabétiques Et Non Diabétiques Dans Les Deumentioning
confidence: 99%
“…In Nigeria, the prevalence of UTI tend to vary depending on the study population and risk factors. For instance, a prevalence of 61.0% was reported among pregnant women (13) while a prevalence of 46% was reported in diabetic patients in Abakaliki (14). Among HIVinfected children and adolescents, a prevalence rate of 32.5% was reported (15) while 43.6% rate was reported in the general population without reported risks for UTI (16).…”
Section: Prévalence Des Infections Urinaires Symptomatiques Et Spectre Bactérien Des Patients Diabétiques Et Non Diabétiques Dans Les Deumentioning
confidence: 99%
“…Globally, it is estimated that about 150 million individuals are affected by urinary tract infections (UTIs) annually, with a significant number of those affected being diabetics [1][2][3]. The 2016 WHO report has shown that there is a marked increase in the number of people affected by diabetes, and this trend is scheduled to grow in geometric proportions in the next couple of decades [4].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus (DM), is a group of metabolic disorders in which there is high blood sugar level over a prolonged period and it is commonly referred to as diabetes [1-10]. Frequent urination, increased thirst, and increased hunger are symptoms of high blood sugar [11][12][13][14][15][16]. Many complications are resulted as a cause of untreated diabetes [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%